Mesenchymal stem cells reduce pain but not degenerative changes in a mono‐iodoacetate rat model of osteoarthritis. Issue 9 (16th May 2014) - van Buul, Gerben M.; Siebelt, Michiel; Leijs, Maarten J. C.; Bos, Pieter Koen; Waarsing, Jan H.; Kops, Nicole; Weinans, Harrie; Verhaar, Jan A. N.; Bernsen, Monique R.; van Osch, Gerjo J. V. M.
ABSTRACT We studied the effects of intra‐articularly injected bone marrow derived mesenchymal stem cells (MSCs), as well as freshly isolated bone marrow mononuclear cells (BMMNCs), on pain, cartilage damage, bone changes and inflammation in an in‐vivo rat osteoarthritis (OA) model. OA was induced unilaterally by injection of mono‐iodoacetate (MIA) and allowed to develop for 3 weeks. Then, animals were treated by intra‐articular injection with MSCs, BMMNCs, or saline as a control. Four weeks later, pain was assessed with an incapitance tester, subchondral bone alterations were measured with µCT and cartilage quality and joint inflammation were assessed by histological analysis. Animals treated with MSCs distributed significantly more weight to the affected limb after treatment, which was not observed in the other groups. No statistically significant differences between treatment groups regarding cartilage damage, subchondral bone alterations and synovial inflammation were observed. Additional cell tracking experiments indicated adequate intra‐articular cell injection and cell survival up to 2 weeks. In our OA model, injected MSCs were able to reduce MIA induced pain, as measured by an increased weight distribution to the affected limb. No statistically significant effects of the cellular therapies on structural damage and synovial inflammation were found. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1167–1174, 2014.